La "documenta" di Kassel : percorsi dell'arte contemporanea - Cestelli Guidi, Anna (Milano : Costa & Nolan srl, 1997)
Lissitzky, El ; Picasso, Pablo ; Lehmbruck, Wilhelm ; Pollock, Jackson ; Nay, Ernst Wilhelm ; Zadkine, Ossip ; Rauschenberg, Robert ; Vedova, Emilio ; Christo ; Rosenquist, James ; Kienholz, Ed ; Thek, Paul ; de Andrea, John ; Byars, James Lee ; Beuys, Joseph ; Merz, Mario ; Serra, Richard ; Paik, Nam June ; Morris, Robert ; Kounellis, Jannis ; Borofsky, Jonathan ; Buren, Daniel ; Schütte, Thomas ; Finlay, Ian Hamilton ; Haacke, Hans ; Lavier, Bertrand ; Ray, Charles ; Kosuth, Joseph ; Kapoor, Anish ; Schütte, Thomas
boek